Analisis Nilai Religius Cerita Rakyat “Masjid Sunan Muria” di Kabupaten Kudus - Maulidia Rahmah; Zumna Afifatun Nisa; Ikna Pradita Oktaviani; Mohammad Kanzunnudin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Folklore is part of cultural history that reflects the past and thoughts of the community, passed down from generation to generation orally or in writing, and contains various values of life. This research is a descriptive qualitative research with a structural approach, aiming to analyze the religious values contained in the folklore “Sunan Muria Mosque” contained in the book “East Coast Folklore” by Mohammad Kanzunnudin, published by CV Adhigama in 2024. The data is a fragment of the story “Masjid Sunan Muria”. The research data are facts about the structure and religious values found in the folklore. The data collection technique used reading and listening methods. Data analysis uses the Miles and Huberman method which consists of data reduction, data presentation, and conclusion drawing. The results of the analysis show that the folklore “Masjid Sunan Muria” contains motifs of shortcomings and shortcomings that can be overcome as well as exemplary religious values, including aspects of belief, worship, knowledge, and practice. Sunan Muria, the main character in the story, shows a strong belief in the teachings of Islam and his ability to practice these values in real actions. The implication of this research is to provide inspiration and learning about the importance of religious values in everyday life and how these values can be applied for the common good.